Caracterização morfológica e divergência genética em acessos de meloeiro - Castro, Jéssica Melina de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The melon is a cucurbit of great economic importance and has high polymorphism in the different characteristics, among which, leaves, flowers and fruits. In order to estimate the genetic divergence among 38 melon access, this study aimed to characterize them morphologically. The study was conducted at the College of Agricultural and Veterinary Sciences (UNESP- FCAV), Campus of Jaboticabal-SP. From September 2014 to January 2015, an experiment was conducted in a randomized block design with four replications, with a total of 608 plants evaluated. The seeds used were provided by the institutions: Embrapa Temperate Climate, Embrapa Vegetables, Rural Federal University of Semi-arid and United States Department of Agriculture. During the growth and development of plants was carried out morphological characterization featuring 35 descriptors used by the Ministry of Agriculture, Livestock and Supply, and three proposed in this paper. Data were assessed by genetic dissimilarity from the Euclidean distance to multicategoric data. With respect to the relative contribution of each character, according to statistics Singh (S.j), five descriptors have stood out with the highest percentage of divergence, as follows: Sex expression; Young fruit: conspicuity of colored grooves; Position of the maximum diameter of the fruit; Seed width and seed color intensity. And by Tocher optimization method, verifying variability among the accessions to the divide into 10 groups. Among the groups, the highlights were the group one by good values for Fruit shape, the four group for Mass (kg), the six group for Soluble Solids (°Brix), the eight group for Firmness and nine group to Internal cavity size. The most divergent pairs were 5 and 20; 6 and 22; 20 and 37; 22 and 37; 26 and 35

O melão é uma cucurbitácea de grande importância econômica e apresenta alto polimorfismo em relação às diversas características morfológicas. Visando estimar a divergência genética entre 38 acessos de meloeiro este trabalho teve por objetivo caracterizar morfologicamente os mesmos. O estudo foi desenvolvido na Faculdade de Ciências Agrárias e Veterinárias (UNESP-FCAV), Câmpus de Jaboticabal-SP. De setembro de 2014 a janeiro de 2015, foi conduzido um experimento no delineamento em blocos casualizados, com quatro repetições, com total de 608 plantas avaliadas. As sementes utilizadas foram cedidas pelas instituições: Embrapa Clima Temperado, Embrapa Hortaliças, Universidade Federal Rural do Semiárido e Departamento de Agricultura dos Estados Unidos. Durante o crescimento e desenvolvimento das plantas foi realizada a caracterização morfológica dispondo de 35 descritores utilizados pelo Ministério da Agricultura, Pecuária e Abastecimento e três propostos neste trabalho. Os dados obtidos foram avaliados através da dissimilaridade genética, a partir da distância Euclidiana para dados multicategóricos. A respeito da contribuição relativa de cada caráter, de acordo com a estatística de Singh (S.j), cinco descritores se destacaram com maior percentual de divergência, sendo eles: Expressão do sexo; Fruto jovem: conspicuidade dos sulcos coloridos; Posição do diâmetro máximo do fruto; Largura da semente e Intensidade da cor de semente. Pelo método de otimização de Tocher, verificou-se variabilidade entre os acessos ao se dividirem em 10 grupos. Dentre os grupos, destacaram-se o grupo um por bons valores para formato do fruto, o grupo quatro para massa (kg), o grupo seis para teor de sólidos solúveis (ºBrix), o grupo oito para firmeza de polpa e o grupo nove para tamanho de cavidade interna. Os pares mais divergentes foram 5 e 20; 6 e 22; 20 e 37; 22 e 37; 26 e 35
Keywords: Melão; Botânica - Morfologia; Genetica vegetal; Polimorfismo (Genetica); Plantas - Analise; Botany Morphology